Management of Technology-Based Learning Innovations in Improving the Quality of Learning at State Madrasah Tsanawiyah 2 Asahan - Fadilah Sari Butar Butar; Hasrian Rudi Setiawan; Indra Prasetia (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
This research aims to describe the management of technology-based learning innovations in improving the quality of learning at MTsN 2 Asahan. This type of research is qualitative with a descriptive research method, where the researcher carries out field research, obtaining data through interview methods, observation and documentation studies. The data that has been collected is analyzed using data reduction, data presentation and drawing conclusions. The validity of the research data was tested using data triangulation techniques. The results of this research conclude that learning innovation necessitates empowerment in the teaching process as an effort to improve the quality of learning. The pandemic period became a turning point in awareness of the empowerment of online learning platforms such as WhatsApp Group (WAG), Zoom, and Google Classroom at MTsN 2 Asahan. This has an impact on teachers' skills in packaging open materials so that they are interesting and easy for students to learn and understand through digital content.